PP.07.27: LIPID-LOWERING AND ANTI-INFLAMMATORY EFFECTS OF OMEGA 3 ETHYL ESTERS AND KRILL OIL. (June 2015) - Cicero, A.F.G.; Rosticci, M.; Morbini, M.; Grandi, E.; Parini, A.; Borghi, C.
Abstract : Objective: The aim of our study was to comparatively evaluate the short-term lipid-lowering efficacy of krill oil and purified Omega 3 ethyl esters PUFAs in mildly overweight hypertriglyceridemic subjects. Design and method: This double blind, randomized clinical trial was carried out in 25 moderately hypertriglyceridemic subjects (TG = 150 - 500 mg/dL). After 4 weeks of diet and physical activity, patients were allocated to treatment with an indistinguishable pill containing Omega 3 ethyl ester PUFAs 2000 mg/die vs. Krill oil 500 mg/die to be assumed once a day. After 4 weeks of treatment, patients were asked to observe a 2-week wash-out period, and they were then assigned to the alternative treatment for a further period of 4 weeks. Results: Although both PUFA sources were able to improve TG plasma levels, esterified omega 3 PUFAs were more efficacious than Krill oil (p < 0.05). Nonetheless, only Krill oil treatment was able to significantly improve HDL-C and apoAI level, both compared to baseline (p < 0.05) and end of treatment with esterified Omega 3 PUFAs (p < 0.05) values. Both treatments were able to significantly reduce hsCRP levels from the baseline (p < 0.05), but Krill oil improved it more efficaciously than esterified omega 3 PUFAs (p < 0.05). Conclusions: Krill oil has lipid-lowering effects comparable with those obtained through a 4 time higher dose of purified Omega 3 ethyl esters PUFAs in mildly overweight hypertriglyceridemic subjects, while more efficaciously reducing hsCRP.